Multidimensional analysis of stigma among female sex workers in Northern Uganda: Principal component and factor analyses. - Kabunga, Amir; Bongomin, Felix; Ayugi, Vella (Sage, 2025)
Background: Female sex workers (FSWs) face significant stigma, which hinders their access to healthcare, social support, and fundamental human rights. Stigma is often compounded by criminalization, violence, and discriminatory attitudes, particularly in low-income regions like Northern Uganda. Objectives: This study aims to analyze the underlying dimensions of stigma among FSWs in Gulu City, Northern Uganda, to provide insights for targeted interventions. Design: A community-based cross-sectional study was conducted from February to March 2023 in Gulu City, Northern Uganda. Methods: A total of 314 FSWs aged 18–49 years participated in the study, yielding a response rate of 83.9%. Participants were recruited using consecutive sampling from hotspots such as bars, brothels, streets, and community health centers. Data were collected through face-to-face interviews using a pre-tested semi-structured questionnaire. Descriptive statistics summarized sociodemographic and economic characteristics. Principal component analysis (PCA) with varimax rotation was applied to identify the primary components of stigma. Factor retention was guided by eigenvalues >1.0, scree plot analysis, and factor loadings ⩾0.35. Reliability was assessed using Cronbach’s alpha. Multivariate analysis examined the association between stigma and demographic variables. Results: The mean age of participants was 28.8 years (standard deviation = 6.4), with most having completed primary education (46.2%). A majority resided in urban areas (93.3%), and 70.7% reported experiencing violence from clients. PCA identified three key dimensions of stigma: social stigma, healthcare-related stigma, and self-stigma. Social stigma encompassed community rejection and discrimination, while healthcare-related stigma involved negative attitudes and experiences within health settings. Self-stigma reflected internalized shame and reduced self-worth among participants. The cumulative variance explained by the three components was 67.2%, with strong internal reliability (Cronbach’s alpha = 0.88). Factors significantly associated with stigma included age, education level, and experience of violence (p < 0.05). Conclusion: The multidimensional nature of stigma among FSWs in Gulu City highlights the urgent need for holistic interventions. Addressing community stigma, improving healthcare provider attitudes, and offering psychosocial support to reduce self-stigma are critical for improving health outcomes and quality of life.
Keywords: Keywords female sex-workers; stigma; Uganda